DIMENSI SAINS DALAM KISAH AL-QUR'AN DAN RELEVANSINYA DENGAN KEAKURATAN PEMILIHAN KATA - Yusuf Baihaqi (IAIN Manado, 2018)
Abstract. Although Al-Qur'an constitutes the book of guidance, it contains many verses related to modern sciences. Advanced scientific development in this modern century makes efforts to connect Al-Qur'an with sciences a must. The relationship between Al-Qur'an and sciences can be seen from some verses related to stories. This is examplified by, for example, the use of the word al-Malik not Fir`awn for the Egypt ruler in the reign of Prophet Josep. Al-Qur'an also uses the word female ant for the leader of ant group that encountered Solomon and its troop. Finally, Al-Qur'an also uses term “three darknesses” in the womb to refer to three stages an infant passed through before its born.Keywords: Al-Qur'an, Story, SciencesAbstrak. Al-Qur'an walaupun diturunkan sebagai kitab suci pemberi petunjuk, akan tetapi termuat dalam kandungannya banyak pembahasan seputar sains. Perkembangan sains di abad modern ini yang sangat pesat, dan keberadaan ayat Al-Qur'an yang sangat banyak yang dapat dikaitkan dengan sains, menjadikan upaya untuk mengaitkan Al-Qur'an dengan sains sebuah keniscayaan. Keterkaitan antara Al-Qur'an dengan sains pun terlihat pada pembahasan ayat-ayat kisah. Bahkan keberadaan sejumlah kata kunci dalam redaksi ayat kisah menguatkan keterkaitan antara Al-Qur'an dan sains, seperti: penyebutan kata “al-Malik” bukan “Fir`aun” untuk menunjukkan penguasa negeri Mesir di era nabi Yusuf as, penyebutan “Semut Betina” bagi pemimpin gerombolan semut yang berpapasan dengan nabi Sulaiman as dan bala tentaranya, dan bahwasannya ada “tiga kegelapan” yang dilalui dan yang meliputi janin prakelahirannya.Kata Kunci: Al-Qur'an, Kisah, Sains